2019
DOI: 10.21608/aps.2019.45119
|View full text |Cite
|
Sign up to set email alerts
|

A Phytochemical Study on Olea europaea L. Olive Leaf Extract (cv. Koroneiki) growing in Egypt

Abstract: Olea europaea is an evergreen tree, native to the Mediterranean region and well known for its edible fruits and oil. Recently much focus has been made on the leaves of the trees due to their high antioxidant property in addition to other therapeutic value. The leaves that are considered by-products during olive oil production are now an essential commodity in the nutraceutical industry. Koroneiki (Olea europaea L. cv Koroneiki) is one of the well-known Greek olive cultivars as the queen of oil-producing olive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Plant phytochemicals or microbial enzymes that serve as reductants are typically responsible for the reduction of metal compounds [18]. Plant extracts containing bioactive alkaloids, phenolic acids, polyphenols, proteins, and carbohydrates are critical first in the reduction and then in the stabilization of metallic ions [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Plant phytochemicals or microbial enzymes that serve as reductants are typically responsible for the reduction of metal compounds [18]. Plant extracts containing bioactive alkaloids, phenolic acids, polyphenols, proteins, and carbohydrates are critical first in the reduction and then in the stabilization of metallic ions [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, olive leaf has been reported as an anti-inflammatory, antioxidant, antithrombotic and antidiabetic agent [2,19,21,22]. In another report, the usage of olive leaves was emphasized as an antioxidant source in pharmaceuticals [23]. Ghomari and co-workers worked on antibacterial activities of phenolic compounds against pathogenic bacteria and demonstrated that oleuropein showed a strong antibacterial activity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Olea europea L. cv. koroneiki is member of the family Oleaceae also known as Queen of olives [1]. It is an ever green, medium sized fruit bearing plant.…”
Section: Introductionmentioning
confidence: 99%